An Emerging Model for Ethical Consumer Behaviour (International Journal of Food and Nutritional Sciences, 2022)
Ethically minded consumer behaviour is a strategic weapon to reach to the goal of sustainable consumption. In the international scenario, ethical consumption is more of consumer’s choice. However, from the purview of a developing economy like India ethical purchase intention is not turned out into actual behaviour. More often decision making environment turns out to be a barrier in this regard. Thereby, the present study proposes a conceptual model exploring the novel concept of ethically minded consumer behaviour reducing the ethical purchase intention-behaviour gap. The study also conceptually visualizes sustainable production and consumption by drawing insights from the broader perspective of sustainable development. The conceptual model thus paves way for the policy makers to adopt policy measures enhancing sustainability through production and consumption patterns